Analisis Faktor Risiko yang Berhubungan dengan Asfiksia pada Bayi Baru Lahir di Rsud Waibakul Kabupaten Sumba Tengah pada Tahun 2023 - Rambu Nurul Siam; Bambang Purwanto; Atika Atika (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Globally, approximately 2.3 million newborn deaths occur within the first 28 days of life, equivalent to around 6,500 deaths each day. This accounts for about 47% of all under-five child deaths, making it a critical concern in global efforts to reduce child mortality. In Indonesia, the infant mortality rate is recorded at 16.85 per 1,000 live births, placing the country third highest in terms of infant mortality among ASEAN countries. One of the leading causes of this high mortality rate is neonatal asphyxia. Objective: This study aims to analyze the risk factors associated with neonatal asphyxia in newborns at Waibakul Regional Hospital, Central Sumba Regency, in 2023. Methods: This study employed a cross-sectional design with a quantitative approach. The population included all infants born at Waibakul Regional Hospital between January and December 2023, totaling 220 newborns. The sample was selected using total sampling. Data were analyzed using the chi-square test. Results: The analysis revealed a significant association between maternal age and neonatal asphyxia (p = 0.016), as well as between fetal distress and neonatal asphyxia (p = 0.001). However, no significant association was found between the mode of delivery and neonatal asphyxia (p = 0.877). Conclusion: Maternal age and fetal distress are significant risk factors associated with the occurrence of neonatal asphyxia. These findings can serve as a basis for healthcare professionals to enhance early detection and prevention efforts for neonatal asphyxia. Keywords: Neonatal asphyxia, maternal age, mode of delivery, fetal distress, risk factors.